ETHNIC CONFLICT THEORY, RELIGIOSITY, AND CULTURAL BOND: APPROACHES COMBINED TO RESOLVE RELIGIOUS INTOLERANCE IN AMBON - Cahyo Pamungkas (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2015)
This study tries to investigate religious intolerance, namely intergroup contact avoidance in Ambon by using i.e. ethnic conflict theory, religiosity, and cultural bond. Ethnic group conflict theory suggests that ethnic and religious identification are more likely related to religious exclusionism due to perceived group threat. Intrinsic religious values and cultural bonds owned by certain communities tend to increase religious harmony, to reduce religious identification and to social boundaries between different religious groups. Ethnic group conflict theory mentions that the stronger the actual competition between ethnic groups at an individual as well as a contextual level, and/or the stronger the perceived ethnic threat, the more the mechanisms of social (contra-) identification will be reinforced, inducing stronger nationalist attitudes and exclusionist reactions. Religiosity in this study refers to concept of pluralistic views of religion and hermeneutic interpretation. Individuals who possess strong religious identification tend to support for religious intolerance due to extrinsic values of religious convictions may contribute to creating intergroup bias. Cultural bond in this study includes traditional alliances between villages, that have different religious affiliation. Such cultural bond, that part of customary laws and contains local wisdom, functions to prevent religious tensions between villages. As theoretical implication of this study is that resolving religious intolerance should use interdisciplinary approaches that consists of cognitive, religious, and cultural dimension.